A practical method to evaluate the thermal efficiency of solar molten salt receivers. (25th May 2021) - Xiao, Gang; Zeng, Jichuan; Nie, Jing
Highlights: An efficient method is proposed to evaluate the efficiency of tower receivers. Detailed analysis is conducted by considering various operating factors. Results by the proposed method agree with the experimental values of Solar Two. Levelized efficiency at design point is used for normalizing various conditions. Application scope of the method is discussed and error analysis is conducted. Abstract: The thermal efficiency of solar molten salt receivers is vital to solar power tower systems. Yet, the related test methods at large-scale application level is still missing. In this paper, a practical method based on direct normal irradiance for the evaluation of thermal efficiency is developed and validated with experimental data. This method mines operating parameters of solar receivers under different irradiance conditions of close-to interval days without affecting the routine control process of the plant. To fully consider the effects of the heliostat field, test time, and ambient conditions, the practical method is further revised, where the thermal efficiency differences of 3.38% and 3.34% are observed at 11:00–11:30 on March 17 and March 22, respectively. Lastly, the design-point condition of the solar receiver is taken into consideration, and the final thermal efficiency (so-called levelized thermal efficiency) reaches 84.20%. This work will facilitate assessing engineering designs at a relatively fair level experimentally and developing practical high-efficiency solar molten salt receivers.